Comparing Prenatal and Postnatal Social Support of Women with Wanted and Unwanted Pregnancies Referring to the Health Centers of Mashhad, Iran - Nahid Jahani Shoorab; Morvarid Irani; khadijeh Mirzaei; Tahereh Sadeghi; Seyed Reza Mazloum; Jamshid Jamali (Journal of Midwifery & Reproductive Health, 2022)
Background & aim: Prenatal and postnatal social support could affect pregnancy consequences, especially the number of wanted pregnancies. This study was performed to compare the social support of women with wanted and unwanted pregnancies referred to the health centers of Mashhad, Iran.Methods: This descriptive cross-sectional study was conducted on 177 pregnant women selected by multistage sampling method in the health centers of Mashhad, from 20th Nov. 2016 to 20th Jan 2017. The pregnant women were classified into two groups, with wanted and unwanted pregnancies at the beginning of pregnancy. They were asked to complete the modified questionnaire of social support during pregnancy. Also, in the second or third visit after birth, they were again asked to complete the modified version of the Postpartum Social Support Questionnaire (PSSQ). Data were analyzed by SPSS software version 27 using T-test, Chi-Square, and MANCOVA.Results: Both the mean score of social support during pregnancy (15.36±.96 VS 14.49±1.33, P<0.000) as well as postnatal social support were higher in wanted compared to unwanted pregnancy groups (161.58 ± 16.90 VS 156.79 ±13.07, P=0.044).Conclusion: The results of this research indicated that mothers with wanted pregnancies had higher social support than unwanted pregnancies; hence, more attention should be paid by specialists and service providers to promote social support in women with unwanted pregnancies.